PENGARUH INTELLECTUAL CAPITAL PADA PEMBERDAYAAN EKONOMI KREATIF DENGAN DIMODERASI PROGRAM PENDAMPINGAN - Irawati, Wiwit; Sugiyanto, Sugiyanto; Nadi, Luh (Lembaga Penerbitan Unversitas Esa Unggul, 2019)
This study aims to prove the influence of Intellectual Capital which is moderated by the Mentoring Program on Creative Economy Empowerment. With the location of the research at the South Tangerang UMKM, this research is motivated by the thought of the importance of the assistance program in the process of empowering the UMKM to be able to lift the people's economy, so that the independence of the UMKM can be achieved in the future. The research method uses Moderated Regression Analysis with data obtained from the questionnaire recapitulation. The results of the study prove that Intellectual Capital has no effect on Creative Economy Empowerment in South Tangerang City with a significance value of 0.581 and the same results are obtained for mentoring programs that also do not directly influence the Creative Economy Empowerment (sig. 0.671). However, Intellectual Capital influences the Empowerment of Creative Economy by strengthening the Mentoring Program with the value of sig. 0.00.Keywords: Intellectual Capital, Mentoring Program, Empowerment of Creative Economy.